La "dissolution" paradoxale du sujet dans la période nietzschéenne de la "maturité" - Nicolas Quérini (Labyrinth: An International Journal for Philosophy, Value Theory and Sociocultural Hermeneutics)
In Nietzsche's "mature" texts, we are witnessing a complete dissolution of the subject. At first glance, however, this appears highly paradoxical (Wotling 2015), leading some commentators to suggest that there is a real contradiction in Nietzsche's work (Gardner 2009), insofar as the author never ceases to speak of himself and at the same time invites his reader to become who he is. Are we to understand, then, that any self is illusory and constitutes a metaphysical illusion, i.e., that the becoming in which we are always caught according to Nietzsche must make any position of a self impossible, and at the very least diminishing? Following in the footsteps of Alexander Nehamas (1985), we believe that we can overcome the contradiction identified by S. Gardner by showing that Nietzsche's conception of the self is not "realistic", but precisely also fictional and dynamically positive at the same time.